How is chocolate made? - Hansen, Grace (2017)
This title will go through the process of how chocolate is made. It will be begin at the cacao tree farms where cacao beans are cleaned and prepped. It will then follow the cacao beans to the manufacturer where they are roasted, winnowed, and turned into delicious chocolate!
Cacao tree farms -- Chocolate factory -- Ready to ship! -- -- More facts.
Includes index.
Ages 4-8
Keywords: Chocolate processing -- Juvenile literature; Cocoa processing -- Juvenile literature; Chocolate -- Juvenile literature